Thermal processing effects on in vitro Antioxidant activities of five common Indian Pulses - Arijita Chakraborty and Sauryya Bhattacharyya (Journal of Applied Pharmaceutical Science, 2014)
Five different types of pulses commonly used in daily cuisine in India, viz. Lentil (Lens culinaris), Green gram (Vigna radiate), Bengal gram (Cicer arietinum), Red kidney beans (Phaseolus vulgaris) and Soybean (Glycine max), were analyzed for their in vitro antioxidant profile before and after thermal processing in water. The thermal processing included methods commonly employed in India for cooking, viz. pressure cooking, microwave treatment, boiling in water and boiling after overnight soaking. The assays performed included ABTS radical decolorization assay, DPPH radical decolorization assay, hydrogen peroxide scavenging assay and hydroxyl radical scavenging assay. The antioxidant profile of the five pulses improved significantly after microwave treatment as evident from all assays except DPPH assay. In case of Bengal gram, improvement was also observed after pressure cooking. In case of soybean, however, apart from microwave treatment, no significant improvement was observed. Enhanced activity of the pulses shown after thermal processing in water might be due to enhanced extraction of polyphenols like gallo-ellagitannins, phenolic acids or flavonoid glycosides, which have less solubility in normal water but enhanced solubility in hot water. The study indicated a systematic approach to ascertain antioxidant quality of pulses after thermal treatment with water.
Keywords: Antioxidant, Lens culinaris, Vigna radiate, Cicer arietinum, Phaseolus vulgaris, Glycine max.